Friends or strangers? Strategic uncertainty and cooperation across experimental games of strategic complements and substitutes - Gabriele Chierchia; Fabio Tufano; Giorgio Coricelli (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2017)
It is commonly assumed that friendship should decrease strategic uncertainty in games involving tacit coordination. However, this has never been tested on two "opposite poles" of coordination, namely, games of strategic complements and substitutes. We present an experimental study having participants interacting with either a friend or a stranger in two classic games: (i.) the stag hunt game, which exhibits strategic complementarity; (ii.) the entry game, which exhibits strategic substitutability. Both games capture a frequent trade-off between a potentially high paying but uncertain action and a lower paying but safe alternative. We find that, relative to strangers, friends exhibit a propensity towards uncertainty in the stag hunt game, but an aversion to uncertainty in the entry game. Friends also "trembled" less than strangers in the stag hunt game but this advantage was lost in the entry game. We further investigate the role of interpersonal similarities and friendship qualities on friendship's differential impact on uncertainty across games of strategic complements and substitutes.
Keywords: C72; C92; D80; 330; coordination; entry game; friendship; strategic complementarity; strategic substitutability; stag hunt game; strategic uncertainty